2015
DOI: 10.1016/j.bbabio.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The specific localizations of phosphorylated Lhcb1 and Lhcb2 isoforms reveal the role of Lhcb2 in the formation of the PSI-LHCII supercomplex in Arabidopsis during state transitions

Abstract: State transitions are an important photosynthetic short-term response that maintains the excitation balance between photosystems I (PSI) and II (PSII). In plants, when PSII is preferentially excited, LHCII, the main heterotrimeric light harvesting complex of PSII, is phosphorylated by the STN7 kinase, detaches from PSII and moves to PSI to equilibrate the relative absorption of the two photosystems (State II). When PSI is preferentially excited LHCII is dephosphorylated by the PPH1 (TAP38) phosphatase, and ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 57 publications
3
61
0
Order By: Relevance
“…Recently, LHCII-PSI-LHCI supercomplexes have been successfully isolated and purified using various detergents (Galka et al, 2012;Drop et al, 2014;Crepin and Caffarri, 2015) or a styrene-maleic acid copolymer (Bell et al, 2015). These findings yielded further insights into the reorganization of supercomplexes associated with state transitions, and it was suggested that phosphorylation of LHCB2 rather than LHCB1 is the essential trigger for the formation of state transition supercomplexes (Leoni et al, 2013;Pietrzykowska et al, 2014;Crepin and Caffarri, 2015;Longoni et al, 2015). Furthermore, characterization of mutants deficient in individual PSI core subunits indicates that PsaH, L, and I are required for docking of LHCII at PSI (Lunde et al, 2000;Zhang and Scheller, 2004;Kouril et al, 2005;Plöchinger et al, 2016).…”
mentioning
confidence: 99%
“…Recently, LHCII-PSI-LHCI supercomplexes have been successfully isolated and purified using various detergents (Galka et al, 2012;Drop et al, 2014;Crepin and Caffarri, 2015) or a styrene-maleic acid copolymer (Bell et al, 2015). These findings yielded further insights into the reorganization of supercomplexes associated with state transitions, and it was suggested that phosphorylation of LHCB2 rather than LHCB1 is the essential trigger for the formation of state transition supercomplexes (Leoni et al, 2013;Pietrzykowska et al, 2014;Crepin and Caffarri, 2015;Longoni et al, 2015). Furthermore, characterization of mutants deficient in individual PSI core subunits indicates that PsaH, L, and I are required for docking of LHCII at PSI (Lunde et al, 2000;Zhang and Scheller, 2004;Kouril et al, 2005;Plöchinger et al, 2016).…”
mentioning
confidence: 99%
“…A proportion of LHC II serves as the antenna of photosystem I in Arabidopsis chloroplasts adapted to increased light intensity (Wientjes et al ). In addition, individual LHC II trimers, termed S and M, remain connected to photosystem II upon phosphorylation, indicating that specific trimers migrate to photosystem I (Wientjes et al , Crepin and Caffarri ). Trimers may be composed of different individual polypeptide chains, giving homotrimers and heterotrimers with specific mobilities and kinetics of phosphorylation (Leoni et al , Pietrzykowska et al , Crepin and Caffarri ).…”
Section: The Photosystem II Supercomplexmentioning
confidence: 99%
“…In addition, individual LHC II trimers, termed S and M, remain connected to photosystem II upon phosphorylation, indicating that specific trimers migrate to photosystem I (Wientjes et al , Crepin and Caffarri ). Trimers may be composed of different individual polypeptide chains, giving homotrimers and heterotrimers with specific mobilities and kinetics of phosphorylation (Leoni et al , Pietrzykowska et al , Crepin and Caffarri ). In Arabidopsis , trimers termed M and S remain bound the photosystem II supercomplex even when phosphorylated on chains Lhcb‐1 and Lhcb‐2 (Crepin and Caffarri ).…”
Section: The Photosystem II Supercomplexmentioning
confidence: 99%
See 2 more Smart Citations